Morquio's syndrome: Clinical and radiological aspects - Aydin, Mustafa; Artaş, Hakan; Ertu?rul, Sabahattin; Yilmaz, Hüseyin (My University, 2006)
Morquio's syndrome is an inherited disorder caused by the lack of the enzyme responsible for breakdown of keratan sulfate. The resulting buildup of keratan sulfate in tissues leads to skeletal dysplasia with other organ systems involvement. A four years old girl brought with the complaints of deformity in legs, abnormal gait, changed shape of chest cage, and short trunk dwarfism was presented to emphasize the clinical and radiological features of the Morquio's syndrome. Morquio's syndrome should be also considered in the differential diagnosis of the patients with short trunk dwarfism and skeletal deformities.
Morquio sendromu: Klinik ve radyolojik yönden de?erlendirme
Keywords: Keratan sulfate; Morquio's syndrome; Radiological finding; Short trunk dwarfism